Formulasi The Living Law Sebagai Pembaharuan Hukum Pidana Nasional Melalui Pendekatan Antropologi Hukum - Manurung, Immanuel Joyson B.; Lubis, Andi Hakim (Media Hukum Indonesia (MHI), 2025)
Adat criminal law, as an integral part of Indonesia’s legal system, is an indigenous legacy that is inseparable from the development of law in the country. In the effort to reform Indonesia’s criminal law and replace the colonial penal code, Adat criminal law has been incorporated into the new Criminal Code (KUHP) as a form of legalization and recognition of its existence. However, this regulation brings consequences for the continuity of customary criminal law itself, particularly concerning the formalization, requirements, and restrictions that are applied. This article examines the impact of the regulation of Adat criminal law in the new Criminal Code that will be implemented. The research employs a legal anthropology approach, part of an empirical methodology, to understand how societal behavior, customs, culture, and emotions in a diverse environment influence and are influenced by the surrounding legal culture. From the study conducted, it is concluded that although the primary goal of regulating customary criminal law in the new Criminal Code is to provide a legal foundation and protection for its application, these regulations may introduce restrictions that could potentially weaken the existence of Adat law. Therefore, a legal foundation is needed that not only acknowledges but also respects and protects Adat criminal law, allowing it to continue to live and develop according to its inherent norms, while still adhering to the nation’s and state’s philosophy.